Crime and the Czech Republic: summary observations - Geis, Gilbert (Crime, law and social change, 1997)
Increased levels of street and organized crime activity have accompanied the transition from totalitarian rule to a freer political climate both in the Soviet Union and in its former east European satellites. A conference in the Czech Republic involving officials from the host country and visiting practitioners and academics largely from the United States considered methods for dealing with burgeoning crime issues. The article summarizes the tone and content of the discussions as well as the substantive issues addressed.